Fanning the flames : fans and consumer culture in contemporary Japan - Kelly, William W. (SUNY series in Japan in transition., 2004)
"Fanning the Flames examines the worlds of fans in the exuberant and commercialized popular culture of contemporary Japan. The works collected here profile denizens of all-night rap clubs; sumo stable patrons: passionate fan clubs of a professional baseball team; enthusiasts of traditional rakugo storytelling; a club of middle-aged female fans of a popular music star; youthful followers of Japan's longest-running rock band; vinyl record collectors; and a thriving community of girls and women who produce and devour amateur comics. Grounded in close, often extended fieldwork with the fans themselves, each case study is an effort to understand both the personal pleasures and political economies of fandoms. The contributors explore the many ways that fans in and of Japanese mass culture actively search for intimacy and identity amid the powerful corporate structures that produce the leisure and entertainment of today's Japan."--Jacket